2013
DOI: 10.1152/ajplung.00426.2012
|View full text |Cite
|
Sign up to set email alerts
|

Efficient delivery of RNA interference oligonucleotides to polarized airway epithelia in vitro

Abstract: Ramachandran S, Krishnamurthy S, Jacobi AM, WohlfordLenane C, Behlke MA, Davidson BL, McCray PB, Jr. Efficient delivery of RNA interference oligonucleotides to polarized airway epithelia in vitro. Am J Physiol Lung Cell Mol Physiol 305: L23-L32, 2013. First published April 26, 2013 doi:10.1152/ajplung.00426.2012.-Polarized and pseudostratified primary airway epithelia present barriers that significantly reduce their transfection efficiency and the efficacy of RNA interference oligonucleotides. This creates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 63 publications
(98 reference statements)
1
39
0
Order By: Relevance
“…Since well-differentiated HAE are very difficult to transfect, in order to achieve acceptable knockdown efficacy we delivered siRNA to freshly seeded, poorly differentiated HAE (29,30). Using this method, we obtained 60% knockdown efficiency for an afadin-specific siRNA relative to expression with a scrambled siRNA negative control (Fig.…”
Section: Comparative Spread Of Four Paramyxoviruses In Haementioning
confidence: 99%
“…Since well-differentiated HAE are very difficult to transfect, in order to achieve acceptable knockdown efficacy we delivered siRNA to freshly seeded, poorly differentiated HAE (29,30). Using this method, we obtained 60% knockdown efficiency for an afadin-specific siRNA relative to expression with a scrambled siRNA negative control (Fig.…”
Section: Comparative Spread Of Four Paramyxoviruses In Haementioning
confidence: 99%
“…Recent studies suggested that strategies designed to interfere with IL-8 gene transcription using transcription factor decoys may have therapeutic potential for CF [5,6]. Small interfering (si)RNAmediated inhibition of IL-8 expression in polarised airway epithelial cells is another strategy [7]; however, interfering in the post-transcriptional regulation of IL-8 is also possible.…”
Section: Introductionmentioning
confidence: 99%
“…Oligonucleotide Transfections-These protocols were described in detail previously (62). Briefly, freshly dissociated human airway epithelial cells, CFBE cells, or HeLa cells were transfected in precoated 96-well plates (Costar) or Transwell TM permeable supports (0.33-cm 2 0.4-m polyester membrane, Costar 3470).…”
Section: Methodsmentioning
confidence: 99%